2019
DOI: 10.1002/jca.21761
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic stability in liver failure patients undergoing therapeutic plasma exchange

Abstract: Introduction: The management of liver failure (LF) remains a challenge for the physician. Therapeutic plasma exchange (TPE) improves consciousness level and tends to normalize hyperkinetic circulation by removing neurotoxic substances from the circulation. Hemodynamic stability is essential for optimal patient management. The objective of this study was to observe the effects of TPE on mean arterial pressure (MAP), vasopressor dependency index (VDI) and vasopressor score (VS) in LF patients. Method: This retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
2
6
0
Order By: Relevance
“…The lower levels of blood indices, such as Hb, HCT, and MCV, might be due to the changes in plasma levels following plasma exchange treatments. Similar studies have shown a fall in blood indices, such as Hbs and HCT, following plasma exchange (21,22). Though, contradictory findings have also been reported (22).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The lower levels of blood indices, such as Hb, HCT, and MCV, might be due to the changes in plasma levels following plasma exchange treatments. Similar studies have shown a fall in blood indices, such as Hbs and HCT, following plasma exchange (21,22). Though, contradictory findings have also been reported (22).…”
Section: Discussionmentioning
confidence: 77%
“…The reason for differences in albumin levels stems from the difference between the control and other groups before 6 starting the treatment. It has also been reported that the serum albumin is significantly increased following plasma exchange (21). However, it has been observed that the LDH levels of patients who underwent hemoperfusion or plasma therapy were significantly higher than control patients.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, PE is the most commonly used mode of ALSS in pediatric patients because of its safety, effectiveness, and ease of operation (32,33). And PE could not merely provide fresh plasma but also eliminate pathogenic and toxic molecules from circulation while restoring coagulation factors (34). Although PE is effective in patients with severe and sudden liver failure, it is frequently limited by plasma availability (35).…”
Section: Discussionmentioning
confidence: 99%
“…When the patients complicated with multi-organ dysfunction, CVVHD(F) was combined with PE. PE can efficiently remove big molecule such as pathogenic cytokines and toxic substances 13,14 . However, PE is often limited due to an inadequate plasma supply 15 and can carry transfusion-related risks.…”
Section: Discussionmentioning
confidence: 99%